CONFLICTED PERSPECTIVES IN GRACILIANO RAMOS’ CHILDHOOD - Furtado, Pedro [UNESP]; Leonel, Maria Célia [UNESP] (FapUNIFESP (SciELO), 2023)
This paper seeks to analyze the development of two conflicted points of view in Graciliano Ramos’ autobiography Childhood. Drawing on Fredric Jameson’s notion of the harmonizing and disharmonizing mechanism of the narrative, in The political unconscious (1992), and on essays about the critical fortune of Childhood, especially those by Alfredo Bosi (2013), we can ascertain, on the one hand, that the adult gaze, which pervades the narration, objectifies the story – mainly reinterpreting the people in the child’s life and criticizing the social order of his childhood. On the other hand, it is clear that the child’s gaze is based on the fragmentary and synesthetic apprehension of the world. The narration through this gaze represents the child’s continuous search for adaptation and protection.
PERSPECTIVAS CONFLITIVAS EM INFÂNCIA, DE GRACILIANO RAMOS
Keywords: autobiography; Childhood; focalization; Graciliano Ramos; narrative harmonization